NUMERICAL SOLUTION OF TIME-FRACTIONAL ORDER FOKKER-PLANCK EQUATION - Prakash, Amit; Kumar, Manoj (TWMS journal of applied and engineering mathematics, 2019)
In this article, new iterative method (NIM) is employed to find the numerical solution of linear and nonlinear time-fractional order Fokker-Planck equation (FPE), which is applied in many fields of engineering and applied science. The introduced technique renders an analytical solution in the form of a convergent series with easily computable components without using any restrictive assumptions. Three numerical examples are tested using this method. Plotted graph illustrate the efficiency and accuracy of the proposed method. Keywords: Fokker-Planck equation; New iterative method (NIM); Analytic solution, Caputo fractional derivative. AMS Subject Classification: 74S30.